HUBUNGAN PERSEPSILANSIA TENTANG KINERJA PENGELOLA DENGAN KEPUASAN LANSIA DI SEKOLAH LANSIA TANGGUH SENIOR SMART KOTA PASURUAN - Asisi Letsoin, Andre; Endah Kurniasih, Dwi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Background: The increasing number of elderly people will cause problems if they get sick. To deal with this problem, one of the efforts made is by providing an Elderly School, which is a type of non-formal education, which is carried out to increase the resilience and welfare of the elderly. So researchers want to examine the relationship between elderly people's perceptions of the performance of elderly school managers and the level of satisfaction of elderly school students. Objective: To determine the relationship between elderly people's perceptions of management performance and elderly satisfaction at the senior smart senior tough school. Research Method: Research design using Cross Sectional. The research population was senior tough senior smart school students with a sample of 150 people, using simple random sampling, collecting data using a questionnaire. Data analysis used the Chi Square Test. Results: The results stated that the manager's performance was good as many as 129 people, of which 117 respondents (90.70%) felt satisfied and 12 respondents (9.30%) felt dissatisfied. Meanwhile, 21 respondents stated that the performance was not good, of which 14 respondents (66.67%) felt satisfied and 7 respondents (33.33) felt less satisfied. Based on the results of statistical tests, it was found that the p-value was 0.002 or p-value <0.05. Conclusion: Based on the results of the Chi Square test calculations, it shows that there is a statistically significant relationship between management performance and elderly satisfaction at the smart senior tough school in Pasuaruan City with P Value = 0.002.Keywords: Elderly, Performance, Satisfaction